Pengaruh perbedaan ukuran mata jaring terhadap hasil tangkapan jaring insang dasar di perairan pantai Difur Kota Tual: The effect of mesh size of bottom gillnet on the total catch in the waters of Difur beach, Tual City - Julianus Ohoiwait; YULIANA A. NGAMEL; ALI RAHANTAN; JULIUS M. RAHANINGMAS; WIWIEN G. HUKUBUN (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2024)
One of the fishing gears that is widely used by fishermen in Dulabetawi village, Difur Beach, Tual City is basic gill net fishing gear and generally uses mesh sizes of 2.5 inches and 1 inch. The aim of this research is to determine the effect of different mesh sizes on the quantity, species composition and size of fish caught with bottom gill nets in the waters of Dulabetawi, Difur Beach. The method used for this research was experimental fishing with 10 operations (trips), namely in the morning and at dusk with a net soaking time of 2-4 hours. The catch data obtained was analyzed using a paired sample t test to determine the effect of using different mesh sizes. varies with weight (grams) and number of fish caught. The results of the paired sample t-test show that the weight (grams) of the total catch is 0.041, which is smaller than 0.05 and for a total of 0.000, it is smaller than 0.05, which means there is a real difference in the use of different mesh sizes on weight ( grams) and the number (heads) of the catch, where the total weight of the catch at a mesh size of 2.5 inches is 40,359 grams and the number of 149 fish is greater than the 1 inch size of 85 fish and a weight of 25,735 grams, which means hypothesis H1 is accepted Hₒ rejected.